Updated Swiss guidelines for the treatment and follow-up of cutaneous melanoma (Swiss Medical Weekly, 2011)
Melanoma is the most common lethal cutaneous neoplasm. In order to harmonise treatment and follow-up of melanoma patients, guidelines for the management of melanoma in Switzerland were inaugurated in 2001 and revised in 2006. A new classification and recent results in randomised trials necessitated changes concerning staging and modifications of the recommendations of therapy and follow-up.